Eating out of home and dietary adequacy in preschool children - Moreira, T. (2015)
The present study aims to describe dietary intake and dietary adequacy according to eating location in preschool children. A sub-sample of 2414 children from the Generation XXI birth cohort (Porto, Portugal), evaluated during the follow-up between 2009 and 2011, was included. Dietary intake was assessed by 3d food diaries and four groups of children were defined according to the eating location: 'Home' (>= 80% of meals at home), 'Other homes', 'Preschool' and 'Restaurants'. A dietary adequacy index was developed based on general recommendations for children; a higher score represents a better dietary adequacy. The comparison of nutrients and foods daily intake according to the eating location groups was performed by ANOVA and ANCOVA to adjust for potential confounders. Children classified in 'Preschool' group ate significantly more vegetables, fruit, bread and fish, and less meat, compared to children classified into the 'Home' group. Children classified in the 'Restaurants' group ate more cakes, salty snacks and fruit juices than children in 'Home' group; and less vegetables, dairy products and pasta/rice/potatoes. In 'Restaurants' children obtained the lowest mean score of the dietary adequacy index (15.5, 95% CI 14.8, 16.3) and in 'Preschool' children had the highest mean score (18.3, 95% CI 18.1, 18.4), corresponding to a better dietary adequacy. Preschools seem to have a relevant role in promoting the intake of healthy foods in preschool children. The consumption in restaurants/coffee shops seems to contribute to energy-dense food intake and reduced consumption of nutrient-dense foods.